Rhizobacteria inoculation in maize associated with nitrogen and zinc fertilization at sowing - Moreno,Andréia de L. (2021)
ABSTRACT Rhizobacteria have a wide range of plant growth-promoting mechanisms of action, making them an alternative and/or complementary biological input for chemical fertilizers. In this respect, the present study aimed to assess growth and nitrogen accumulation in maize plants as a function of Azospirillum brasilense, Bacillus subtilis, zinc and nitrogen application at sowing. The experiment with the ‘AL Bandeirante’ maize variety was conducted in a greenhouse, using a completely randomized design. The treatments were arranged in a 2 x 2 x 2 x 2 factorial scheme, with six repetitions, considering the presence and absence of Azospirillum brasilense (5 g kg-1), Bacillus subtilis (5 mL kg-1) and zinc (20 g kg-1) in the seeds and addition or not of nitrogen (30 kg ha-1) to the soil. The variables assessed were plant height, stem diameter, leaf, stem, shoot, root and total dry weight, and shoot nitrogen content. Nitrogen fertilization in the absence of zinc increased shoot and total dry weight as well as shoot nitrogen content. Zinc applied to the seeds improved the total and stem dry weight of maize plants in the absence of Bacillus subtilis. Inoculation with Azospirillum brasilense and Bacillus subtilis increased the stem diameter and shoot nitrogen content of maize plants when nitrogen fertilization was not performed at sowing. There was no isolated or interaction effect between factors for plant height and root dry weight.